Indigenous women, work, and history, 1940-1980 - McCallum, Mary Jane Logan, 1974- (Critical studies in native history ;, 2014)
Based on a range of sources including the records of the Departments of Indian Affairs and National Health and Welfare, interviews. print, and media, McCallum shows how state-run education and placement programs were part of Canada's larger vision of assimilation and extinguishment of treaty obligations. Conversely, she also shows how Indigenous women link these same programs to their social and cultural responsibilities of community building and state resistance.